Gas exchanges in the zucchini culture fertilized with biofertilizers in two types of soil - de Azevedo, Josimar; de Araújo Viana, Thales Vinícius; Gomes, Krishna Ribeiro; Gomes de Sousa, Geocleber; Moreira de Azevedo, Benito; Lino Chagas, Keivia (Comunicata Scientiae, 2021)
The application of biofertilizers may provide plants similar performance and even superior to the use of mineral fertilizers, therefore, the determination of the most suitable sources to be applied in different crops is relevant. Given the importance of gas exchange in the performance of crops and that biofertilizers can provide increases in these physiological parameters, this study aimed to evaluate gas exchange in zucchini plants cultivated in two types of soil and managed with different aerobic fermentation biofertilizers. The experiment was carried out in full sunlight, in pots, using a randomized blocks design in an arrangement of split plots. The plots consisted of two types of soil (S1: Red-Yellow Argisol and S2: Fluvic Neossol), subdivided plots into five aerobic fermentation biofertilizers (F1 = quail, F2 = sheep, F3 = mixed - bovine + quail + sheep, F4 = bovine, and F5 = enriched crab), with five replicates. At 45 days after transplanting, the following variables were analyzed: photosynthesis, stomatal conductance, transpiration, internal CO2 concentration, leaf temperature, and chlorophyll. Bovine, sheep, and mixed biofertilizers showed the highest rates with the best performance of Italian zucchini cultivation. The types of soil studied concerning the rates did not have a significant effect between treatments on zucchini cultivation. Moreover, Chlorophyll was not significantly influenced by any of the treatments applied.